The Job That Calls My Name: Theoretical Explanations for Gendered Wording in Job Advertising and the Importance of Recruitment Communication: A Literature Review - Szabó, Kincső (Filológia.hu, 2024)
One of the main goals of a (young) job seeker is to find a job that offers a valuable opportunity in their career and that also satisfies the professional curiosity. One of the most frequently visited labour market platforms for this purpose are job advertising portals. Browsing through job advertisements is a much more complex process than it may seem at first sight: numerous studies show that a job advertisement is usually the first encounter between the employer’s offer and the expectations of the potential candidate. The primary goal of recruitment communication is to attract all job seekers who match the description in the advertisement, however, discriminatory references and implicit cues referring to one gender may be unconsciously coded into language, which therefore distorts equal application opportunity. The aim of this literature review is to synthetise the emergence, functioning and social implications of implicit gender references in job advertisements. The article introduces the topic through six main sections, broken down into theoretical components. The introduction is followed by a discussion of the gender gap at both national as well as international level, the basic principles of recruitment communication, the main explanatory theories of organisational behaviour, the effects of implicit gender references on the perceiver, and lastly, a discussion of gender linguistics is touched upon.